Treatment of Central Serous Chorioretinopathy with Carbonic Anhydrase Inhibitor - Riani Witjaksana; Vera Sumual (Majalah Oftalmologi Indonesia, 2016)
Background: To report a case of central serous chorioretinopathy at Ophthalmology Department ofRD Kandou Hospital, Manado.Case Illustration: A 51-year-old male patient came to hospital with complaint of sudden blurredvision in his right eye since 1 week before admission. He felt there was a black shadow in the center ofhis right eye. He had history of uncontrolled hypertension and smoking for the last 30 years.Examination result showed that visual acuity of his right was 1/60. On confrontation test, there wascentral scotoma in the right eye with normal extra-ocular motility and he had a relative afferentpupillary defect. On fundus examination, there was an area of pigment near the fovea and elevatedcentral macula and consisted with subretinal fluid. Patient was treated with carbonic anhydraseinhibitor (CAI) as long as one week. During the follow-up, there was an improvement in his visual acuity.Conclusion: After treatment of acetazolamide as long as one week, CSCR looked improved in visualacuity and decreased subretinal fluid. Generally, CSCR have a good prognosis.Keywords: central serous chorioretinopathy, acetazolamide, subretinal fluid